2017
DOI: 10.1038/cddiscovery.2017.10
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-1 inhibition attenuates profibrotic signaling in hypoxia-induced pulmonary fibrosis

Abstract: Idiopathic pulmonary fibrosis (IPF) is characterized by lung remodeling arising from epithelial injury, aberrant fibroblast growth, and excessive deposition of extracellular matrix. Repeated epithelial injury elicits abnormal wound repair and lung remodeling, often associated with alveolar collapse and edema, leading to focal hypoxia. Here, we demonstrate that hypoxia is a physiological insult that contributes to pulmonary fibrosis (PF) and define its molecular roles in profibrotic activation of lung epithelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 66 publications
2
38
0
Order By: Relevance
“…The final stage of healing focuses on remodeling the scar and regaining normal tissue function. These dynamic processes describes the tissue remodeling (Galectin‐1, Fibulin 3) seen in our study . The protein microarray of rat lung homogenates with BPD also demonstrated cell survival properties after MSC delivery.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The final stage of healing focuses on remodeling the scar and regaining normal tissue function. These dynamic processes describes the tissue remodeling (Galectin‐1, Fibulin 3) seen in our study . The protein microarray of rat lung homogenates with BPD also demonstrated cell survival properties after MSC delivery.…”
Section: Discussionsupporting
confidence: 62%
“…These dynamic processes describes the tissue remodeling (Galectin-1, Fibulin 3) seen in our study. 74,75 The protein microarray of rat lung homogenates with BPD also demonstrated cell survival properties after MSC delivery. For example, osteoprotegerin and WISP-1 support cell survival in TNF-induced apoptotic events and while prolactin is known for its role in reproductive functions it is also contains anti-apoptotic properties.…”
Section: Discussionmentioning
confidence: 96%
“…were considered to be significantly related to IPF and NSCLC. Focal adhesion was considered as a key pathway shared by blue module and turquoise module, and many gens/proteins have been considered to be involved in the progression of IPF through disordering focal adhesion (Gimenez et al, 2017;Kathiriya et al, 2017;Molina-Molina et al, 2018). For example, it has been reported that decreased expression of collagen VI, an important kind of protein of ECM, would upregulate the focal adhesion (Knueppel et al, 2018).…”
Section: Disscusionmentioning
confidence: 99%
“…In addition to angiogenesis, galectin-1 has also been reported to be involved in mesenchymal activity via SMAD2 signaling in various cells, including gastric cancer cells, pancreatic stellate cells, and fibroblasts (19)(20)(21). Galectin-1 induced the phosphorylation of SMAD2 through its molecular interaction with SMAD2 in lung fibroblasts (19), thus promoting pulmonary fibrosis (19,22). As concerns the eye, however, there have been no data reported on the profibrotic role of galectin-1 in fibrogenic disorders such as neovascular AMD.…”
mentioning
confidence: 99%